EXTENDED ESSAY OF PSYCHOLOGICAL IMPACTS TOWARD RAPE VICTIMS IN “TIL IT HAPPENS TO YOU” MUSIC VIDEO BY LADY GAGA - Wijayanti, Annisa Retno (LANTERN (Journal on English Language, Culture and Literature), 2016)
“Til It Happens To You” is a song by Lady Gaga. The lyrics and the musicvideo tell about the story of women who have been raped in their college life.The purpose of this study is to analyze the elements of the poetry in the lyricsand to show the readers the psychological contents as portrayed in the musicvideo. The study is limited on two aspects, which are textual and contextualaspects. Figurative devices and dictions are used to analyze the textual aspects;meanwhile the contextual aspects use psychoanalysis theory. Library researchis done to compile the data. The finding of this study is psychological impactstoward the rape victims, which are reflected in the lyrics and in the music videoof “Til It Happens To You”.